Analysis of Antibody Response to Invariable Regions of VlsE, the Variable Surface Antigen of Borrelia burgdorferi - Liang, Fang Ting (American Society for Microbiology (ASM), 1999)
VlsE, the variable surface antigen of Borrelia burgdorferi, consists of two invariable domains at the amino and carboxyl termini and one central variable domain. The latter contains six invariable regions, IR(1) to IR(6), and six variable regions. In the present study, the antigenicity of all of the invariable regions in B. burgdorferi-infected monkeys, humans, and mice was assessed by peptide-based enzyme-linked immunosorbent assays. Only one invariable region, IR(6), was antigenic in all animals of the three host species. IR(2) and IR(4) were also antigenic in mice.